The Renin-Angiotensin-Aldosterone System as a Therapeutic Target in Late Injury Caused by Ischemia-Reperfusion - Simón Quetzalcóatl Rodríguez-Lara; Leonel García-Benavides; Alejandra Guillermina Miranda-Díaz (International Journal of Endocrinology)
Ischemia-reperfusion (I/R) injury is a well-known phenomenon that involves different pathophysiological processes. Connection in diverse systems of survival brings about cellular dysfunction or even apoptosis. One of the survival systems of the cells, to the assault caused by ischemia, is the activation of the renin-angiotensin-aldosterone system (also known as an axis), which is focused on activating diverse signaling pathways to favor adaptation to the decrease in metabolic supports caused by the hypoxia. In trying to adapt to the I/R event, great changes occur that unchain cellular dysfunction with the capacity to lead to cell death, which translates into a poor prognosis due to the progression of dysfunction of the cellular activity. The search for the understanding of the diverse therapeutic alternatives in molecular coupling could favor the prognosis and evolution of patients who are subject to the I/R process.